Consumer Attitudes toward Ready–To–Eat Packed Food Items (With Special Reference to Jaffna Divisional Secretariat Division) - Meenambekai, R.; Selvarajan, P. (Faculty of Management and Finance, University of Colombo, Sri Lanka, 2012)
Ready- to- Eat packed food items play a key role among the people in today’s busy lifestyle. It is observed that there is a huge flow of products into the consumer market in Jaffna district after the post conflict period. This research study attempted to identify the consumer attitudes toward the Ready- to- Eat packed food products (R2E) in Jaffna DS division. The problem associated with this research study is to describe consumer attitudes towards the above said food items. The main objective of this study is to identify factors (demographic factors and behavioral factors) influencing on consumer attitudes towards these products. For this purpose, 100 respondents were selected by using Area Probability Sampling method with an association of Judgment Sampling and data gathered from them through questionnaire and personal interviewing. The data analysis covered percentage, frequency, rank order and cross tab analyses by using the version 16.0 of SPSS package. The findings showed the majority of the consumers for these products were young generation people especially students and working people below 45 years who belongs to nuclear family with moderate monthly income level. It was also found that television was the major source of medium for consumer awareness, and the interest of consumer towards these products was instant consumption, timesaving, taste and convenience to use them as snacks. Health consciousness was the major factor indicated by the non-buyers of these products. Moreover planned purchase was common among majority of the elders while impulse buying behavior is shown among many consumers preferred milk based products. Therefore it is recommended that these food manufacturers should pay much attention on attractive packaging, health and nutrients and quality and intermediaries should stress on effective sales promotion activities to increase the consumption of these products and sustainability.
Keywords: Consumer Attitudes; Impulsive buying; Planned purchase; Ready- to- Eat food items